Research on Fibroblast Growth Factor 21 and Its Relationship to Patients with Polycystic Ovary Syndrome and Obesity - Koçaslan D; Kısakol G (Diabetes, Metabolic Syndrome and Obesity)
Derya Koçaslan,1 Gürcan Kısakol2 1Department of Geriatrics, Trabzon Kanuni Training and Research Hospital, Trabzon, Turkey; 2Department of Endocrinology and Metabolism, Bursa Yüksek Ihtisas Training and Research Hospital, Bursa, TurkeyCorrespondence: Derya Koçaslan, Trabzon Kanuni Training and Research Hospital, Department of Geriatrics, İnönü Mah Merkez Numune Kampüsü, Kahramanmaraş Cd., Ortahisar/Trabzon, 61250, Türkiye, Email deryakocaslan@gmail.comPurpose: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder, and the role of fibroblast growth factor 21 (FGF21), a metabolic regulator, in its pathophysiology remains unclear. In this context, this study aims to evaluate the FGF21 levels in women with PCOS compared to healthy control subjects and investigate the relationship between FGF21 and obesity.Patients and Methods: The population of this prospective, non-randomized, controlled study comprised consecutive female patients aged 18– 55 years who presented to the outpatient clinics of a tertiary hospital between October 2017 and February 2018. At least two of the three parameters of the Rotterdam Consensus Criteria were regarded in diagnosing PCOS. Ninety-two patients with (n=62) and without PCOS (n=30) were categorized based on their BMI values. Participants’ serum FGF21 levels were measured, and the relationships between FGF21 levels and parameters such as age, body mass index (BMI), waist circumference, body fat percentage, and homeostasis model assessment insulin resistance (HOMA-IR) were analyzed. The study’s primary and secondary outcomes were the difference in serum FGF21 levels between the patient and control groups and the impact of obesity on FGF21 levels in both groups.Results: The median age of the patient group was significantly lower than the control group (31.5 years vs 24.0 years, p< 0.001). There was also a significant difference between the groups in HOMA-IR (p=0.020). On the other hand, there was no significant difference between the groups in FGF21 level (p> 0.05). Analysis revealed no significant effects of age or HOMA-IR on FGF21 levels. BMI had a marginal impact on FGF21 levels regardless of PCOS status. Statistically significant positive correlations between FGF21 and DHEAS were detected in the study population (rho=0.282, p=0.007) and all PCOS patients (rho=0.364, p=0.004).Conclusion: FGF21 does not appear to play a significant role in the pathophysiology of PCOS or its associated metabolic abnormalities.Plain Language Summary: PCOS affects many women worldwide, causing irregular periods and metabolic problems. Scientists have been studying various proteins that might explain how PCOS develops. One such protein, FGF21, helps control blood sugar and fat metabolism. This study compared FGF21 levels between women with and without PCOS. We found that FGF21 levels were similar in both groups and unrelated to weight or blood sugar control, suggesting that FGF21 might not be as important in PCOS as previously thought.Keywords: obesity, insulin resistance, metabolic syndrome, hyperandrogenism, body mass index, hormones